Icons of Egyptian Art: Crowns and Headdresses of Female Royalty in Amarna Iconography - del Barrio Madruga, Belén (Eikón / Imago, 2023)
The art of the Amarna Period presents some unconventional features with a unique artistic style in Egyptian culture. Queen Nefertiti plays a fundamental role in Amarna iconography. No other queen is depicted with such frequency, and it is remarkable how her figure as queen evolves throughout the reign of Akhenaten, breaking certain canons historically established for Egyptian royalty. One of the most significant and emblematic attributes of royalty is the crown, an ornament of gods and kings. The review of the iconography, following a timeline, and the analysis of the different crowns worn by the queen throughout the Amarna period, constitute an indicator of the importance that she is acquiring, as well as a line of investigation to try to determine the power that she holds in each of those moments.